The Effect Of Postpartum Self-Care Education On Preventing Postpartual Infections In Postparum Mothers In The Work Area Of Mongeudong Public Health Center - Wulandari Wulandari; Fitriani Fitriani; Fitra Yani; Juwita Maulani; Putri Eka Sari; Rohana Rohana (CV. AFDIFAL MAJU BERKAH, 2026)
The postpartum period is a critical phase for maternal health, as women undergo physical, psychological, and social recovery while being vulnerable to complications, particularly postpartum infections. Postpartum infections remain a significant contributor to maternal morbidity and mortality, especially in low- and middle-income countries, and are often associated with inadequate hygiene practices, delayed detection, and limited self-care knowledge. This study aimed to analyze the effect of postpartum self-care education on the prevention of postpartum infections among postpartum mothers in the working area of the Mongeudong Public Health Center, Lhokseumawe City. This study employed a quantitative quasi-experimental design with a pretest–posttest control group approach. A total of 60 postpartum mothers were selected using purposive sampling and divided into an intervention group (n = 30) and a control group (n = 30). Data were collected using structured questionnaires to assess knowledge and attitudes, observation sheets to measure compliance with self-care practices, and clinical observations to identify postpartum infections. Statistical analyses included univariate analysis, Wilcoxon and Mann–Whitney tests, and logistic regression. The results showed a significant improvement in maternal knowledge, attitudes, and compliance with postpartum self-care practices after the educational intervention (p < 0.05). The incidence of postpartum infection was significantly lower in the intervention group (8%) compared to the control group (32%). Postpartum self-care education was found to be a significant factor in reducing the risk of postpartum infections. In conclusion, structured postpartum self-care education is effective in improving maternal knowledge, attitudes, and compliance, and in preventing postpartum infections. This intervention is recommended to be implemented as a routine program in primary healthcare services to enhance maternal health outcomes and reduce postpartum morbidity.